The development of comic media based on Sekujang culture for elementary school students - Atika Susanti; Abdul Muktadir; Ady Darmansyah (Universitas Papua, 2025)
Elementary students' cognitive learning outcomes remain a challenge, particularly in understanding, remembering, and applying taught concepts. Low cognitive achievement is often caused by a lack of student engagement, unappealing teaching methods, and minimal use of interactive and contextual learning media. This study aims to develop and assess the feasibility of Sekujang culture-based comic media and determine its effectiveness in enhancing students' cognitive learning outcomes in Bahasa Indonesia learning. Using the R&D method with the ADDIE model, this study found that the comic media met the